Responding to the Shifting Interest in Elementary Level Islamic Education with Religious Moderation - Budiono, Budiono (STAI MA'ARIF MAGETAN, INDONESIA, 2023)
The shift in the paradigm of society to send their children to public elementary schools is caused by the implementation of religious education which is considered lacking by the community. Meanwhile, the community really needs a larger portion of religious education for their children. Along with this need, MIN/SDI is present in the community by offering more and more balanced hours of religious education. This then gives more interest to the community to send their children to MIN/SDI. So that their need for a balanced education between general science and religion can be fulfilled with religious education institutions added religious moderation as a perspective in the millennial century.